Marine n-3 Fatty Acids and Gene Expression in Peripheral Blood Mononuclear Cells - Ulven, Stine M. (Springer US, 2014)
Intake of marine n-3 fatty acids has been shown to have beneficial effects on cardiovascular disease. Gene expression analyses in peripheral blood mononuclear cells (PBMCs) are used to understand the underlying mechanisms of action of marine n-3 fatty acids. The aim of this review was to summarize the effects mediated by marine n-3 fatty acids on gene expression in PBMCs. A systematic literature search was conducted in PubMed in May 2014 and 14 papers were included. Targeted gene expression studies were reported in 9 papers and focused on genes involved in lipid metabolism and inflammation. Whole genome transcriptome analyses were conducted in 5 papers, and processes and pathways related to atherosclerotic plaque formation such as inflammation, oxidative stress response, cell cycle, cell adhesion, and apoptosis were modulated after fish oil supplementation. PBMC gene expression profiling has a potential to clarify further the molecular effects of fish oil consumption on human health.